Sociodemographic and clinicopathological profile of 80 cases of oral squamous cell carcinoma - Carolina Emerick; Tamires G. Magalhães; Maria Carolina L. J. M. Barki; Lívia R. Crescencio; Renata Tucci; Eleni Maria V. B. Barros; Rebeca S. Azevedo (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT Objective: To describe demographic and clinicopathologic profile of oral squamous cell carcinoma (OSCC) cases from incisional biopsies collected at the Nova Friburgo Health Institute of the Fluminense Federal University [Instituto de Saúde de Nova Friburgo da Universidade Federal Fluminense (ISNF/UFF)] and at the Raul Sertã Municipal Hospital [Hospital Municipal Raul Sertã (HMRS)]. Methods: Oral Pathology Laboratory records from the ISNF/UFF were reviewed and all cases of OSCC were primarily selected. Cases from ISNF/UFF and HMRS were selected and had their demographic data collected from the medical records. Clinical characteristics were evaluated using the images of the lesions taken on the biopsy day and the laboratory files. The histological slides were later reviewed. Results: Eighty cases of OSCC were identified. Most patients were male (56.7%), with a mean age of 60 years, smoker (62.71%) and/or alcoholic (44.55%). The most affected anatomic site was the tongue (39.49%), presenting mainly as an ulcer (39.49%). Microscopically, the well-differentiated lesions were more common (35.44%), and the mean counting of mitoses was 5.5/10 high-power field. Conclusion: The profile of OSCC patients in Nova Friburgo partly reflects the world literature, with emphasis on the following differences: low average number of mitoses found in the histopathological analysis and prevalence of well-differentiated lesions. Such differences may be a result of the characteristic variations of the local population, reinforcing the importance of conducting epidemiological studies that demonstrate OSCC peculiarities in different regions.